Temporal shifts in gyrA mutation types and sublineage replacement in ST11 Salmonella enterica serovar Enteritidis over a decade (2014–2023): A genomic epidemiological study in Guangxi, China - Xianying Zeng; Lanqi Li; Lanxin Zhao; Jianyun Zhao; Menghan Li; Ruicheng Zheng; Mengmeng Shi; Dongmei Tan; Shaoting Li; Yang Wang; Yongning Wu; Li Bai (Food Research International, 2026)

Antibiotic-induced photosynthetic dysfunction in wheat: Coupled inhibition of light reactions and carbon assimilation revealed by multi-omics - Jin Wu; Wen Ye; Jiayin Zhou; Yaxin Zhu; Qing Wei; Zhiheng Li; Lidan Wu; Huijun Liu; Shaoting Du (Environmental Pollution, 2026)

Heterogeneity analysis of extracellular vesicles from four edible crops: structural characteristics and functional evaluation - Shuhong Li; Kefan Guo; Yuning Song; Shaoting Yuan; Guiyun Chen; Ye Chen (Food Chemistry, 2026)

Geographical origin authentication of whole garlic using 16S ribosomal RNA profiling of garlic microbiota and machine learning - Zhihan Xian; Shaoting Li; David A. Mann; Xiangyu Deng (Food Microbiology, 2026)

The effect of environmental concern on consumers’ preferences for carbon-neutral-labeled dairy: Evidence from China - Qi Liu; Shaoting Li; Yanjun Ren; Jens-Peter Loy (Journal of Environmental Management, 2026)

Hyphomicrobiales-mediated C–S coupling underpins enantiomeric differences in soil nutrient cycling induced by the chiral herbicide napropamide - Yuying Wang; Ran Wu; Shijie Cui; Qinghua Ma; Yanzhe Dong; Xintong Li; Lukuan Huang; Yaxin Zhu; Miaozhen Cai; Shaoting Du (Journal of Hazardous Materials, 2026)

Preparation of a novel flavin-adsorbing biocarrier and its accelerating mechanism on anaerobic bioreduction of 3-nitrobenzenesulfonate - Ze Fu; Hong Lu; Shaoting Zhuo; Jichao Wang; Qiansheng Li; Xiaona Li; Haikun Zhang (Journal of Environmental Chemical Engineering, 2026)

UV-328 disrupts mineral nutrient homeostasis and secondary metabolism in Arabidopsis thaliana: Linking physiological responses to molecular mechanisms - Ying Wang; Yaxin Zhu; Xintong Li; Qinghua Ma; Lukuan Huang; Ran Wu; Miaozhen Cai; Shaoting Du (Environmental Pollution, 2026)

Nano-silicon mitigates sulfamethoxazole-induced stress in wheat seedlings: Integrated transcriptomic and metabolomic analysis - Qianqian Liu; Ziting Jin; Xinyu Liao; Jie Feng; Zhiheng Li; Wenlu Zhao; Yaxin Zhu; Ran Wu; Shaoting Du; Huijun Liu (Journal of Environmental Chemical Engineering, 2025)

DeepSANet: A deep learning approach for hierarchical geographical source attribution of Salmonella - Shan Liang; Shaohui Mei; Jiahao Ji; Bingkui Li; Mingyuan Xu; Miaomiao Chen; Yawen Huang; Yuxin Zheng; Di Chen; Xiangyu Deng; Shaoting Li; Hongmei Zhang (Food Research International, 2025)

Spatiotemporal decoupling of land surface temperature driving mechanisms using ensemble learning - Ai Wang; Daofeng Liu; Zijing Li; Shaoting Liu; Yunfei Nie; Qiang Zhang (Sustainable Cities and Society, 2025)

Isolation, evolution, and biological characterization of non-virulent and non-drug-resistant Escherichia coli from porcine intestine - Bingming Ou; Biyang Xiao; Qingqing Li; Jiayi Wang; Xue Lin; Weinan Zhong; Huimin Zhu; Yufu Liu; Shaoting Li; Hongmei Zhang; Wenhua Liu; Minyu Zhang (Folia Microbiologica, 2025)

Single-cell RNA Sequencing Demonstrates the Heterogeneity of Different Molecular Subtypes in Gastric Cancer - Ming Ren; Hongyan Ma; Lijia Guo; Yuqing Liu; Li Wang; Shaoting Wei (Biochemical Genetics, 2025)

Engineered macrophage-targeted germacrone-bearing nanosheet achieves synergistic treatment of acute kidney injury through macrophage polarization modulation and oxidative stress alleviation - Yunguang Wang; Shaoting Wang; Qikai Luo; Yourou Zhou; Xingchen Li; Yiwei Shang; HuaiYu Wang; Egor Y. Plotnikov; Xinyu Liao; Wei Feng; Qiang He; Juan Jin (Chemical Engineering Journal, 2025)

Cell-permeable PI3 kinase competitive peptide inhibits KIT mutant mediated tumorigenesis of gastrointestinal stromal tumor (GIST) - Zongying Jiang; Yue Guo; Jun Shi; Shaoting Zhang; Liangying Zhang; Yapeng Wang; Guofu Li; Ru Bai; Hui Zhao; Jianmin Sun (Molecular Biology Reports, 2024)

Effects of sand substrate removal on the intestinal antioxidant and metabolism in Marsupenaeus japonicus - Kuangcheng Zhao; Shaoting Jia; Junxia Wang; Xueqiong Bian; Shibo Chen; Jitao Li; Ping Liu; Jian Li; Yuefeng Cai; Xianyun Ren (Fish & Shellfish Immunology, 2024)

ABA-importing transporter (AIT1) synergies enhances exogenous ABA minimize heavy metals accumulations in Arabidopsis - Yaxin Zhu; Yue You; Shihao Zheng; Jiaxin Li; Yuying Wang; Ran Wu; Zhiguo Fang; Huijun Liu; Shaoting Du (Journal of Hazardous Materials, 2024)

A dose-dependent effect of UV-328 on photosynthesis: Exploring light harvesting and UV-B sensing mechanisms - Yaxin Zhu; Hua Wang; Xiaobo Xiang; Kashif Hayat; Ran Wu; Jiaying Tian; Haoyi Zheng; Minghui Xie; Beier Li; Shaoting Du (Journal of Hazardous Materials, 2024)

Recent advances in viability detection of foodborne pathogens in milk and dairy products - Yan Qi; Shaoting Li; Yilin Zhang; Chunping You (Food Control, 2024)

Changes in glacier surface temperature across the Third Pole from 2000 to 2021 - Shaoting Ren; Tandong Yao; Wei Yang; Evan S. Miles; Huabiao Zhao; Meilin Zhu; Shenghai Li (Remote Sensing of Environment, 2024)

Consumers' willingness to pay for carbon-labeled agricultural products and its effect on greenhouse gas emissions: Evidence from beef products in urban China - Xuan Chen; Shihang Zhen; Shaoting Li; Jieyu Yang; Yanjun Ren (Environmental Impact Assessment Review, 2024)

Effect of RpoS on the survival, induction, resuscitation, morphology, and gene expression of viable but non-culturable Salmonella Enteritidis in powdered infant formula - Zhuolin Ma; Weiying Xu; Shaoting Li; Siyi Chen; Yuheng Yang; Zefeng Li; Tong Xing; Zepeng Zhao; Dongping Hou; Qingqing Li; Ziying Lu; Hongmei Zhang (International Journal of Food Microbiology, 2024)

Ketoprofen exposure perturbs nitrogen assimilation and ATP synthesis in rice roots: An integrated metabolome and microbiome analysis - Huan Wang; Zhiheng Li; Luoqin Shen; Ping Zhang; Yanyao Lin; Xinting Huang; Shaoting Du; Huijun Liu (Environmental Pollution, 2023)

Plant growth-promoting rhizobacteria: A good companion for heavy metal phytoremediation - Yaxin Zhu; Yu Wang; Xiaolin He; Beier Li; Shaoting Du (Chemosphere, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

miR-181a targets PTEN to mediate the neuronal injury caused by oxygen-glucose deprivation and reoxygenation - Shengnan Li; Peiyi Zhu; Yajun Wang; Shaoting Huang; Zhaochun Wu; Jiawen He; Xingjuan Hu; Ying Wang; Yanquan Yuan; Bin Zhao; Guoda Ma; You Li (Metabolic Brain Disease, 2023)

Enhanced degradation of pharmaceuticals in wastewater by coupled radical and non-radical pathways: Further unravelling kinetics and mechanism - Fu Liu; Hongzhou Li; Shaoting Lei; Qingmiao Yu; Hongqiang Ren; Jinju Geng (Journal of Hazardous Materials, 2023)

Prediction of pharmaceuticals removal in activated sludge system under different operational parameters using an extended ASM-PhACs model - Xiang Li; Shaoting Lei; Gang Wu; Qingmiao Yu; Ke Xu; Hongqiang Ren; Yanru Wang; Jinju Geng (Science of The Total Environment, 2023)

The effect of air exposure and re-water on gill microstructure and molecular regulation of Pacific white shrimp Penaeus vannamei - Qiong Wang; Qianqian Ge; Zhao Chen; Jiajia Wang; Shaoting Jia; Yuying He; Jitao Li; Zhiqiang Chang; Jian Li (Fish & Shellfish Immunology, 2023)

Circ_0101802 Facilitates Colorectal Cancer Progression Depending on the Regulation of miR-665/DVL3 Signaling - Jun Li; Xinbin Liu; Shaoting Dong; Haojie Liao; Weizhen Huang; Xia Yuan (Biochemical Genetics, 2022)

Comparative transcriptomic analysis and validation of the ovary and testis in the ridgetail white prawn (Exopalaemon carinicauda) - Shaoting Jia; Ling Jin; Jianjian Lv; Jiajia Wang; Jitao Li; Ping Liu; Jian Li (Frontiers in Marine Science, 2022)
The ridgetail white prawn, Exopalaemon carinicauda is an important cultured seawater species in China. As female E.carinicauda grows faster than males, it is significant to search for the differentially expressed genes (DEGs) between males and females. However, there is no public available E.carinicauda genome data, and genes related to E. carinicauda sex differences are unclear. In this study, the transcriptome sequencing for ovary and testis tissues of E. carinicauda were conducted, and 20,891 DEGs were identified including 11,709 up-regulated DEGs and 9,182 downregulated DEGs. The functional categories related to meiosis and reproduction were enriched as well as the steroidogenesis KEGG pathway was clustered. Furthermore, the genes related to male reproduction and cell cycle were dug out which were verified by real-time PCR. In addition, two-color fluorescent in situ hybridization result showed that foxj1b might play roles during early stage of the ovary development. Therefore, our result provides clues for the study of genes related to reproduction and sex difference in E.carinicauda .

Toxicity effect of the edible pigment carmoisine on Polyrhachis vicina Roger (Hymenoptera: Formicidae) - Ziyu Li; Jing Zhang; Shaoting Yin; Gengsi Xi (Ecotoxicology, 2022)

Analysis on the spatio-temporal evolution and influencing factors of China’s grain production - Shaoting Li; Daojun Zhang; Yuan Xie; Chao Yang (Environmental Science and Pollution Research, 2022)

Evidences of Z- and W-Linked Regions on the Genome of Fenneropenaeus chinensis - Qiong Wang; Jianjian Lv; Xianyun Ren; Jiajia Wang; Shaoting Jia; Yuying He; Jian Li (Frontiers in Marine Science, 2021)
Fenneropenaeus chinensis is a commercially cultured shrimp in China. F. chinensis adults show significant sexual dimorphism, with larger females than males. However, sex determination (SD) of F. chinensis has not yet been elucidated. Clarification of the sex-determining system of F. chinensis could enrich our knowledge of the sex differentiation mechanism in crustaceans and facilitate the study of sex-controlling technologies. Here, we studied the sex-determining system of F. chinensis using the fixation index ( F ST ) between the sexes to detect the genetic differentiation in resequencing data of multiple males and females. We located the candidate sex chromosome in the genome of F. chinensis and concluded the female heterogametic (ZW) SD system. We also assembled female-specific sequences, which could be used as molecular markers to identify the sex of F. chinensis . However, the differentiation of the F. chinensis Z and W chromosome is limited. RNA-seq data detected many genes with male-biased expression in the Z-specific region, which possibly could further intensify the divergency between the Z and W chromosomes.

Ultrahigh Temperature Metamorphic Record of Pelitic Granulites in the Huangtuyao Area of the Huai’an Complex, North China Craton - Shaoting Ma; Xu-Ping Li; Hao Liu; Fanmei Kong; Han Wang (Journal of Earth Science, 2019)

Large-scale Exploration of Neuronal Morphologies Using Deep Learning and Augmented Reality - Zhongyu Li; Erik Butler; Kang Li; Aidong Lu; Shuiwang Ji; Shaoting Zhang (Neuroinformatics, 2018)

Effects of dietary supplementation with algal astaxanthin on growth, pigmentation, and antioxidant capacity of the blood parrot ( Cichlasoma citrinellum × Cichlasoma synspilum ) - Feng Li; Shuiying Huang; Xiaoxia Lu; Jun Wang; Mingwei Lin; Yu An; Shaoting Wu; Minggang Cai (Journal of Oceanology and Limnology, 2018)